IMPROVEMENT OF VISIONARY LEADERSHIP FOR THE HEADMASTERS OF PRIVATE MADRASAH ALIYAH - Sugiarti, Diyah Yuli (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The aim of research is to improve the visioner leadership for head master of private Madrasah Aliyah.Research method use qualitative description. Data is taken by interview with some teachers of Madrasah Aliyah in Beasi city. Research result is 80% from head masters of privat Madrasah Aliyah in Bekasi city don’t have visioner leadership.That condition needs solution. The private Madrasah Aliyah in Bekasi needs improvement of visioner leadership to manage school in Globalization.